EFFECTIVE MULTITASK DEEP LEARNING FOR IOT MALWARE DETECTION AND IDENTIFICATION USING BEHAVIORAL - Vishnu Bannurkar; Jayendra Kumar; Dr. G. Vishnu Murthy (Utilitas Mathematica, 2025)
This program emphasizes the protection of our expanding network of intelligent devices. The IoT device in residential, health and other industries requires the need to ensure these network technologies. Technological progress also increases related risks. We examine the domain of attacks on malware, including prominent cases such as Botnet Mirai. By understanding these risks, we want to develop effective countermeasures. This initiative has two goals. We create resistant security solutions specially designed for IoT devices.